2022
DOI: 10.3390/microorganisms10102033
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Hemolytic Activity of Mesophilic Aeromonas salmonicida SRW-OG1 Is Brought about by Elevated Temperatures

Abstract: Aeromonas salmonicida is a well-known cold-water pathogenic bacterium. Previously, we reported the first isolation of pathogenic A. salmonicida from diseased Epinephelus coioides, a kind of warm-water fish, and it was proved to be a putative mesophilic strain with potent pathogenicity to humans. In order to investigate the mechanisms underlying mesophilic growth ability and virulence, the transcriptome of A. salmonicida SRW-OG1 at 18, 28, and 37 °C was analyzed. The transcriptome of A. salmonicida SRW-OG1 at d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(28 citation statements)
references
References 87 publications
0
26
0
2
Order By: Relevance
“…T2SS functions as a transport mechanism to translocate proteins (such as aerolysin, proteases, DNases and amylases) from the periplasm to the extracellular environment in Aeromonas (Li et al, 2011; Seshadri et al, 2006), and the ExeAB homologue GspAB complex has been demonstrated to be functional in the assembly of the T2SS secretin multimer in A. salmonicida (Strozen et al, 2011). The haemolytic genes aerA and hlyA have been found to be significantly up‐regulated in mesophilic A. salmonicida SRW‐OG1 grown at 28 and 37°C compared to 18°C (Chen et al, 2022), and the haemolytic activity of A. salmonicida is enhanced by elevated incubation temperature or limited iron (Chen et al, 2022; Kroniger et al, 2022). It can be thought that these common virulence factors constitute the basic virulence of A. salmonicida .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…T2SS functions as a transport mechanism to translocate proteins (such as aerolysin, proteases, DNases and amylases) from the periplasm to the extracellular environment in Aeromonas (Li et al, 2011; Seshadri et al, 2006), and the ExeAB homologue GspAB complex has been demonstrated to be functional in the assembly of the T2SS secretin multimer in A. salmonicida (Strozen et al, 2011). The haemolytic genes aerA and hlyA have been found to be significantly up‐regulated in mesophilic A. salmonicida SRW‐OG1 grown at 28 and 37°C compared to 18°C (Chen et al, 2022), and the haemolytic activity of A. salmonicida is enhanced by elevated incubation temperature or limited iron (Chen et al, 2022; Kroniger et al, 2022). It can be thought that these common virulence factors constitute the basic virulence of A. salmonicida .…”
Section: Discussionmentioning
confidence: 99%
“…. In particular, it is worth noting that, more and more studies in China on infection (Lian et al, 2020;Meng et al, 2020;Wang et al, 2020), pathogenicity (Chen et al, 2022;Meng et al, 2017;Yi et al, 2022) and interaction with hosts of A. salmonicida (Huang, Qi, Zuo, Alias, & Xu, 2020;Long et al, 2015;Xia et al, 2022;Xue et al, 2021) have been reported in recent years, implying the popularity and importance of this bacterium in China.…”
mentioning
confidence: 99%
“…According to our recently published study, the A. salmonicida SRW-OG1 contains the aerolysin and hemolysin ( 5 ). In the present study, the hemolysis activity of A. salmonicida SRW-OG1 wild-type, znuA -RNAi, znuB -RNAi and znuC -RNAi strains were compared.…”
Section: Resultsmentioning
confidence: 99%
“…The isolation of C947 strains from patients with acute gastroenteritis and the isolation of AJ83 strains from patients with post-traumatic cellulitis of the foot ( 12 ). Based on pathogen-host interaction factor analysis by Qi et al ( 13 ) against A. salmonicida SRW-OG1, C947, and AJ83 strains and transcriptome data analysis by Chen et al ( 5 ) on A. salmonicida SRW-OG1 at different temperatures, A. salmonicida SRW-OG1 has a great potential to infect mammals and humans. Notably, the remarkably high expression of znuA, znuB , and znuC genes at 18 and 37°C also indicated that they might be related to the pathogenesis under different temperatures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation